MEMBANGUN KEPUASAN PELANGGAN INDIHOME TELKOM WITEL KUDUS DENGAN MENINGKATKAN PERSEPSI HARGA, LAYANAN PURNA JUAL, DAN PROMOSI - Fauziyah, Atikah Nur; Tjahjaningsih, Endang (Proceeding SENDI_U, 2021)
The study aims to examine and analyze the effect of price perception, after sales service, and promotion on customer satisfaction at Telkom Witel Kudus. The population is Indihome’s customer in Kudus Regency and this study take a sample of 100 respondents. The sampling technique in this study used purposive sampling. The data used in this study takes a primary data, with a questionnaire as a research instrument. The analytical tools used is multiple linear regression, validity test, reliability test, F test, coefficient of determination test (Adjusted R Square), which is then processed by calculation of SPSS 21. The results showed price perception, after sales service and promotion has a positve effect and significant on customer satisfaction.